Melindungi Konsumen Melalui Regulasi: Studi Kasus Sosialisasi Peraturan BPOM Tentang Batas Cemaran Kosmetik - Kashuri, Mohamad (UIN Syarif Hidayatullah Jakarta, 2025)
This study evaluates the effectiveness of disseminating BPOM Regulation No. 16 of 2024 in enhancing stakeholder understanding and support for regulations designed to protect consumers from unsafe cosmetics. The regulation aims to align national standards with international ones; however, its implementation faces significant challenges. Using a descriptive quantitative approach, a survey was conducted with 528 participants in a hybrid-format dissemination program. The results indicate that the dissemination activities were effective, with an average evaluation score of 5.19 out of 6 for the regulation, and consumer protection aspects receiving the highest score (5.40). The implementation of the activities was rated as excellent (average score of 5.39), reflecting the organizers’ success in reaching a broad audience. However, challenges related to implementation costs were identified as barriers, particularly for MSMEs. These businesses require technical guidance and operational support. The study concludes that the dissemination activities improved stakeholder preparedness, but successful implementation requires a collaborative approach involving technical assistance, adequate time allocation for discussions, and innovative delivery methods. These measures are crucial to support a safe and globally competitive Indonesian cosmetics industry.